1998
DOI: 10.1002/hep.510280515
|View full text |Cite
|
Sign up to set email alerts
|

Splenorenal Shunt Blood Flow by Transit–Time Ultrasound As An Index of Collateral Circulation in Portal Hypertensive Rats

Abstract: The aim of this study was to develop a technique that could serve as an index of portosystemic shunt (PSS) blood flow in portal hypertensive rats whose main shunt is the splenorenal shunt (SRS). The main hemodynamic measurements performed were: SRS blood flow by the transit-time ultrasound (TTU) method, percentage of PSS, and regional blood flows by the microsphere method. We determined the accuracy and reproducibility of SRS blood flow measurements under baseline and pharmacological (octreotide) conditions. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The preventive effect on the development of the collateral venous circulation predominates the action of vasomotor effect, because the low outflow values of SRS-BF, despite the development of hepatic fibrosis, strongly suggest an effect on the development of collateral circulation for two reasons: First, such dramatic hemodynamic data have never been observed in acute or chronic delayed administration, that is, when fibrosis or PHT was already acquired. Second, these values of SRS-BF are similar to that observed in baseline conditions in normal rats [20,21]. Moreover, the macroscopic aspect of SRS in treated rats was similar to normal rats.…”
Section: Hemodynamicssupporting
confidence: 77%
See 2 more Smart Citations
“…The preventive effect on the development of the collateral venous circulation predominates the action of vasomotor effect, because the low outflow values of SRS-BF, despite the development of hepatic fibrosis, strongly suggest an effect on the development of collateral circulation for two reasons: First, such dramatic hemodynamic data have never been observed in acute or chronic delayed administration, that is, when fibrosis or PHT was already acquired. Second, these values of SRS-BF are similar to that observed in baseline conditions in normal rats [20,21]. Moreover, the macroscopic aspect of SRS in treated rats was similar to normal rats.…”
Section: Hemodynamicssupporting
confidence: 77%
“…The SRS is the main collecting vessel of the collateral circulation in portal hypertensive rats [23]. The determination of SRS-BF by TTU method was shown as an accurate index of collateral circulation, which was well correlated with the quantification of PSS by a microspheres method [20]. A TTU method appears more suitable than a microsphere method.…”
Section: Hemodynamicsmentioning
confidence: 98%
See 1 more Smart Citation
“…The changes of portal pressure and the flow and diameter of SRS were determined at 1, 4, 7, 10, and 14 days after ligation surgery (n = 6, 6, 6, 7, and 9 in each PVL group, respectively) or sham operation (n = 6, 6, 6, 4, and 8 in each sham group, respectively). The portal pressure was measured by the catheterization method and subsequently the SRS flow was detected by transit-time ultrasound (TTU) in individual rats at the scheduled day [14]. The resistance of SRS (R-SRS) was calculated from SRS flow and portal pressure.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…It drains portal blood flow into inferior vena cava via left renal vein [11][12][13]. It was reported that the SRS flow may reflect the flow of portal-systemic collaterals [14,15]. In well-established portal hypertensive rats, SRS flow positively correlated with portal pressure and the extent of hepatic fibrosis [15].…”
Section: Introductionmentioning
confidence: 98%